2018
DOI: 10.1038/s41598-018-31608-x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus infection changes Aedes aegypti oviposition olfactory preferences

Abstract: Aedes aegypti mosquitoes, main vectors for numerous flaviviruses, have olfactory preferences and are capable of olfactory learning especially when seeking their required environmental conditions to lay their eggs. In this study, we showed that semiochemical conditions during Aedes aegypti larval rearing affected future female choice for oviposition: water-reared mosquitoes preferred to lay eggs in water or p-cresol containers, while skatole reared mosquitoes preferred skatole sites. Using two independent behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
0
25
1
Order By: Relevance
“…Contrary to what has been described previously [33,78], only three members of the chemosensory gene families were differentially regulated in response to a change in infection status. While previous studies have demonstrated a connection between behavioral sensitivity and an increased transcript abundance of select ORs and OBPs [33,34], this study identified IR75k.1 as the only chemosensory gene to change (decrease) in response to DENV-1 infection. The orthologue, AgamIR75k, in Anopheles gambiae has been shown to respond to short chain carboxylic acids [79,80], which regulate host seeking in mosquitoes [81,82].…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Contrary to what has been described previously [33,78], only three members of the chemosensory gene families were differentially regulated in response to a change in infection status. While previous studies have demonstrated a connection between behavioral sensitivity and an increased transcript abundance of select ORs and OBPs [33,34], this study identified IR75k.1 as the only chemosensory gene to change (decrease) in response to DENV-1 infection. The orthologue, AgamIR75k, in Anopheles gambiae has been shown to respond to short chain carboxylic acids [79,80], which regulate host seeking in mosquitoes [81,82].…”
Section: Discussioncontrasting
confidence: 67%
“…While DENV-2 infection has been shown to affect the odor-mediated oviposition behavior of gravid Ae . aegypti [ 34 ], such an effect has not yet been described for the characteristic odor-mediated behavior of host seeking females.…”
Section: Introductionmentioning
confidence: 99%
“…Apparently, several chemicals activate this sensillum (Table 2), indicating that they are putative infochemicals mediating oviposition behavior in mosquitoes (Liu et al 2018). Some of these chemicals have already been shown to mediate oviposition behavior in mosquitoes through behavioral assays (Eneh et al 2016b, Gaburro et al 2018. Such compounds are 3-methylindole, 2-ethylphenol, 4-ethylphenol, and 4-methylphenol (Table 3).…”
Section: Mechanisms Of Odor Reception and Signal Transductionmentioning
confidence: 99%
“…Arbovirus infection may also be associated with changes in the expression of other categories of biological processes, such as arbovirus infection changes in Ae. aegypti blood feeding behavior and oviposition olfactory preferences [46,47,48].…”
Section: Introductionmentioning
confidence: 99%